Pengaruh Kompetensi dan Beban Kerja terhadap Kinerja Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Toraja Utara - Yulianah Heni; Althon K. Pongtuluran; Randi Tangdialla (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Employee performance is one of the key determinants of organizational effectiveness in delivering high-quality public services. Improving public service performance depends not only on administrative systems but also on employee competencies and the organization's ability to manage workloads appropriately. This study aims to examine the influence of competence and workload on employee performance at the Population and Civil Registration Office of North Toraja Regency. A quantitative descriptive approach was employed. The study involved all 48 employees, consisting of civil servants and government employees under work agreements, using a saturated sampling technique. Data were collected through observation, interviews, documentation, and structured questionnaires measured using a five-point Likert scale. Data analysis was performed using IBM SPSS Statistics version 23, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial (t-test), simultaneous (F-test), and coefficient of determination analysis. The findings indicate that competence has a positive and significant effect on employee performance. Workload also positively influences employee performance as long as it remains proportional to employees' capabilities and responsibilities. Simultaneously, competence and workload significantly affect employee performance. These findings emphasize that strengthening employee competencies while maintaining a balanced workload contributes to higher organizational effectiveness and improved public service quality. The study provides empirical evidence supporting the importance of human resource development and workload management in enhancing employee performance within public sector organizations.